The gene : an intimate history - Mukherjee, Siddhartha (New York : Scribner, 2016)
"The story of the gene begins in earnest in an obscure Augustinian abbey in Moravia in 1856 where Gregor Mendel, a monk working with pea plants, stumbles on the idea of a "unit of heredity." It intersects with Darwin's theory of evolution, and collides with the horrors of Nazi eugenics in the 1940s. The gene transforms postwar biology. It invades discourses concerning race and identity and provides startling answers to some of the most potent questions coursing through our political and cultural realms. It reorganizes our understanding of sexuality, gender identity, sexual orientation, temperament, choice, and free will, thus raising the most urgent questions affecting our personal realms. Above all, the story of the gene is driven by human ingenuity and obsessive minds -- from Gregor Mendel and Charles Darwin to Francis Crick, James Watson, and Rosalind Franklin to the thousands of scientists working today to understand the code of codes. Author of the Pulitzer Prize-winning bestseller The Emperor of All Maladies, Mukherjee draws on his scientific knowledge and research to describe the magisterial history of a scientific idea. Woven through The Gene is the story of Mukherjee's own family and its recurring pattern of schizophrenia, a haunting reminder that the science of genetics is not confined to the laboratory but is vitally relevant to everyday lives. The moral complexity of genetics reverberates even more urgently today as we learn to "read" and "write" the human genome -- unleashing the potential to change the fates and identities of our children and our children's children."--Jacket.
"Magnificent, beautifully written, and riveting, Siddhartha Mukherjee's The Gene: An Intimate History illuminates the quest to decipher the master-code of instructions that makes and defines humans; that governs our form, function, and fate; and that determines the future of our children."--Lead into summary on Book Jacket.
Prologue: Families -- The "missing science of heredity" 1865-1935 -- "In the sum of the parts, there are only the parts" 1930-1970 -- "The dreams of geneticists" 1970-2001 -- "The proper study of mankind is man" 1970-2005 -- Through the looking glass 2001-2015 -- Post-genome 2015- ... -- Epilogue: Bheda, Abheda -- Glossary -- Timeline.
Includes bibliographical references (pages 551-554) and index.
The Washington Post 10 best books, 2016
The New York Times Book Review 100 Notable Books, 2016
Keywords: Mukherjee, Siddhartha -- Family -- Health; Buck, Carrie, -- 1906-1983.; Genetics -- History; Genes; Heredity; Medical ethics -- History; Genetics -- History